Pembatasan Masa Jabatan Presiden Sebagai Upaya Menghindari Terjadinya Abuse of Power - Yudhistira, Elsan (Al-Ishlah: Jurnal Ilmiah Hukum, 2020)
President term limitation is an effort to prevent a President who takes control of the nation for a long time because the President will make it possible to abuse power. Presidential term limitation is a crucial thing to be regulated because it will make the potential abuse of power, and the authoritarian government will grow in some countries. In every nation, we can see adopting a presidential system organize about Presidential term limitation to President's candidate. Seeing that there are several types adopted by various countries that adopt the Presidential system, then it will be studied which system is the best system to decrease the possibility of the occurrence abuse of power performed by the President. The research method uses a statue approach, a historical approach, and a conceptual approach. The results of this study indicate that of the 20 (twenty) countries that adhere to the presidential system, it shows that the most widely used method is only one re-election and no re-election because with this system it is supposed that it can easily limit the term of office of the President and also can be determine fixed government. The chance of abusing power will reduce, while the system No Immediate re-election and No limitation re-election is a country that allows it to be in control for a long time without any restrictions to run for President so that the possibility of abuse of authority will be more open.